Well-Being in the Nordic Countries: An International Comparison - Ólafsson, Stefán (Veftímaritið Stjórnmál og stjórnsýsla, 2013)
This study asks how well the Nordic nations have managed in a new social environment of globalization, increasing competition and new challenges to the Nordic welfare model? The focus is on well-being outcomes, rather than on welfare inputs (expenditure generosity or rights and institutional features). For this purpose we have constructed a data bank with well-being measures for 29 modern nations, based on 69 variables in 9 well-being dimensions. With this data we have constructed an overall well-being index and sub-indexes for these nations. We find that in terms of well-being outcomes the Nordic nations (including Iceland) share major patterns of well-being characteristics. In a data-driven clustering analysis (with Dendograms, using the Ward Method) of all the 69 variables, our well-being outcomes cluster the nations in a way comparable to Francis Castles’ families of nations and Esping-Andersen’s main welfare regime types. We disaggregate the outcomes by clusters and well-being dimensions.The findings indicate that the five Nordic nations had the highest level of well-being amongst modern nations during the period from 2005 to 2008, along with Netherlands, Switzerland and Luxembourg. The strength of the Nordic cluster of nations seems to be their emphasis on equality of income distribution, poverty reduction, improving family conditions and facilitating social cohesion and participation, while also promoting economic strength and a high affluence level. The study also assesses correlates of well-being amongst these nations, including welfare state generosity, political influences, social trust, strength of democracy and distributional characteristics. The findings support a narrative emphasizing the importance of lifting the worse off up the well-being ladder of society. That seems to be the most efficient strategy for improving the overall well-being of modern nations.